2006
DOI: 10.1111/j.1744-7909.2006.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Farnesyl Diphosphate Synthase Gene fromTaxus mediaRehder: Cloning, Characterization and Functional Complementation

Abstract: Farnesyl diphosphate synthase (FPS; EC 2.5.1.10) catalyzes the production of 15-carbon farnesyl diphosphate which is a branch-point intermediate for many terpenoids. This reaction is considered to be a ratelimiting step in terpenoid biosynthesis. Here we report for the first time the cloning of a new full-length cDNA encoding farnesyl diphosphate synthase from a gymnosperm plant species, Taxus media Rehder, designated as TmFPS1. The full-length cDNA of TmFPS1 (GenBank accession number: AY461811) was 1 464 bp w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…FPPS catalyzed reaction occurs in two consecutive steps; condensation of isopentanyl diphosphate (IPP) with dimethylallyl diphosphate (DMAPP) to form 10-C intermediate geranyl diphosphate (GPP) and condensation of GPP with another molecule of IPP which results into 15-C FPP. This gene has been characterized from variety of plant species including Arabidopsis (Closa et al 2010), Artemisia (Matsushita et al 1996), Hevea (Takaya et al 2003), maize (Cervantes et al 2006), rice (Sanmiya et al 1997) and Taxus media (Liao et al 2006). It has been shown that overexpression of ginseng farnesyl diphosphate synthase in Centella asiatica hairy roots enhanced phytosterol and triterpene biosynthesis .…”
Section: Introductionmentioning
confidence: 97%
“…FPPS catalyzed reaction occurs in two consecutive steps; condensation of isopentanyl diphosphate (IPP) with dimethylallyl diphosphate (DMAPP) to form 10-C intermediate geranyl diphosphate (GPP) and condensation of GPP with another molecule of IPP which results into 15-C FPP. This gene has been characterized from variety of plant species including Arabidopsis (Closa et al 2010), Artemisia (Matsushita et al 1996), Hevea (Takaya et al 2003), maize (Cervantes et al 2006), rice (Sanmiya et al 1997) and Taxus media (Liao et al 2006). It has been shown that overexpression of ginseng farnesyl diphosphate synthase in Centella asiatica hairy roots enhanced phytosterol and triterpene biosynthesis .…”
Section: Introductionmentioning
confidence: 97%
“…roseus improved catharanthine production . The plastidial MEP pathway provides the general acyclic 5‐carbon isopentenyl pyrophosphate (IPP) and dimethylallyl pyrophosphate (DMAPP) for biosynthesis of terpenoids, especially monoterpenoids and diterpenoids . Ajmalicine belongs to the family of monoterpene indole alkaloids, so the MEP pathway also provides its precursors theoretically.…”
Section: Introductionmentioning
confidence: 99%
“…FPS plays a key role [ 30 32 ] in the catalytic reaction in isoprenoid biosynthesis; this step is considered rate-limiting. In the present study, we reported the molecular characterisation of two FPS genes from T .…”
Section: Discussionmentioning
confidence: 99%
“…wilfordii . The analysis of FPS gene expression patterns in various plants demonstrated not only that the gene expression is tissue-specific [ 33 34 ] but also that the isoprenoid derivative contents increase [ 20 , 30 , 35 38 ]. The gene expression analysis showed that FPS genes could increase the isoprenoid substance contents in the plants [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%